Dynamic stability evaluation of underground tunnels based on deformation reinforcement theory. (October 2018) - Liu, Yaoru; Wu, Zheshu; Yang, Qiang; Leng, Kuangdai
Highlights: A dynamic stability evaluation method is presented based on deformation reinforcement theory. An object-oriented 3D nonlinear finite element program TFINE is developed. Two indicators presented are more intuitive in characterizing stability. The proposed method has been well applied in tunnels. Abstract: Owing to the rapid and increasing application of underground engineering, the stability of underground tunnels under complex geological and seismic environments is receiving increasing attention. Seismic stability analysis and reinforcement design are important to guarantee engineering safety and operation. Based on the deformation reinforcement theory, a dynamic analysis method of the anti-seismic stability evaluation of underground tunnels is presented. The time history of plastic complementary energy norm is used to identify the instant when the structure is exhibiting the most devastating failure. The unbalanced force is used to represent the local failure of the structure. The reinforcement forces are derived through the distribution of unbalanced forces at the instant with the maximum PCE norm. These evaluation indices are incorporated into a three-dimensional nonlinear finite element analysis program, TFINE, which is designed by an object-oriented approach. Further, an elastoplastic integration algorithm and a comprehensive convergence rule are implemented. Examples of a single tunnel and parallel tunnels subject to earthquake are demonstrated, showing the capability and effectiveness of TFINE in evaluating the structure stability.